Evaluation of anti-inflammatory activity of Cissampelos pareira root in rats - Amresh G.; Reddy G.D.; Rao Ch.V.; Singh P.N. (My University, 2025)
In the present study, 50% ethanolic extract of Cissampelos pareira roots (CPE) in acute, subacute and chronic models of inflammation was assessed in rats. Per os (p.o.) administration of CPE (200, 400 mg/kg) exhibited significant anti-inflammatory activity. In acute inflammation as produced by carrageenin 59.55% and 64.04%, by histamine 15.38% and 30.77%, by 5-hydroxytryptamine 17.78% and 31.11% and by prostaglandin E2-induced hind paw edema 19.23% and 30.77% protection was observed. While in subacute anti-inflammatory models using formaldehyde-induced hind paw edema (after 1.5 h) 38.36% and 47.95% and in chronic anti-inflammatory model using cotton pellet granuloma 15.02% and 19.19% protection from inflammation was observed. CPE did not show any sign of toxicity and mortality up to a dose level of 1000 mg/kg, p.o. in rats. Both acute as well as chronic administration of CPE (100, 200 and 400 mg/kg, p.o.) did not produce any gastric lesion in rats. These data indicate that CPE possesses significant anti-inflammatory activity without ulcerogenic activity suggesting its potential as an anti-inflammatory agent for use in the treatment of various inflammatory diseases. © 2006 Elsevier Ireland Ltd. All rights reserved.